PEMANFAATAN DAUN MENGKUDU (Morinda citrifolia L) YANG DI FERMENTASI SEBAGAI SUBSTITUSI UNTUK MAKANAN IKAN TAMBAKAN (Colossoma macropomum) - Ahmad Afif Alam; Adelina Adelina; Benny Heltonika (Berkala Perikanan Terubuk, 2017)
Looking for alternative material from other resource to substitution of flour in feed of fish have done in early time. This research was conducted on June - August 2016. Aimed of ths study was to determine the amount of fermented flour from Morinda citrifolia L in the feed which affect the growth, feed efficiency, feed digestibility and protein retention in tambaqui (Colossoma macropomum). This research used a completely randomized design (CRD) with one factor, 5 treatments and 3 replications. The treatment with substitution of soybean flour (SF) with fermented Morinda citrifolia L leaf flour (MF) were Controls (100% SF: 0% MF), P1 (90% SF: 10% MF), P2 (85% SF : 15% MF), P3 (80% SF : 20% MF), P4 (75% SF : 25% MF), contain of protein in the feed about 30%. Results this study showed that the best result was treatment P3 (80: 20%)with a specific growth rate of 3.03% / day, feed efficiency rate of 30.6%, 78.86% of feed digestibility and protein retention 24.99%.